Cancer and inflammation: Differentiation by USPIO‐enhanced MR imaging. Issue 3 (30th May 2013) - Seyfer, Perla; Pagenstecher, Axel; Mandic, Robert; Klose, Klaus‐Jochen; Heverhagen, Johannes T.
<x xml:space="preserve">Abstract</x> Purpose To assess ultrasmall superparamagnetic iron oxide particles (USPIO) ‐enhanced MR imaging for the differentiation of malignant from benign, inflammatory lesions. Materials and Methods In this study, approved by the local animal care committee, VX2 carcinoma and intramuscular abscesses were implanted into the hind thighs of New Zealand White rabbits. MR imaging was performed pre contrast and serially for 24 h after the injection of USPIO. MR findings were compared with histopathologic results based on Prussian blue stains for the presence of iron. Results Twenty‐four hours after the Ferumoxtran‐injection, no changes were observed in VX2 carcinomas, whereas a mean reduction of the contrast‐to‐noise ratio (CNR) of approximately 90% was noticed in abscesses as well as in necrotic tumors. On histopathologic examination, abscess and necrotic parts of the tumor were found to include iron‐containing monocytes demonstrating that the reduction in CNR was caused by USPIO‐tagged monocytes. Conclusion Our results prove the ability of USPIO‐enhanced MRI to differentiate benign, inflammatory from malignant lesions. J. Magn. Reson. Imaging 2014;39:665–672. © 2013 Wiley Periodicals, Inc.